AN ANALYTICAL STUDY AND RELATION OF ACADEMIC INVOLVEMENT OF TEACHERS IN SCHOOLS EDUCATION OF BIHAR: A RESULT (International Journal of Food and Nutritional Sciences, 2022)
Currently, the state of teacher education in Bihar is in its initial stages of transformation. Progress has been made, but there is still a considerable distance to cover. The advancement of teacher education necessitates the collective effort of various stakeholders, including experts from within and outside the state. The cornerstone of this progress lies in strengthening and solidifying teacher education programs within the state's universities.While Bihar boasts an adequate number of trained teachers, the focus must shift towards ensuring the quality of their training. Elevating public awareness about education is pivotal in this endeavor. Furthermore, deeper research in the field of education is imperative. Collaborations with reputable organizations, both domestic and international, can play a pivotal role in guiding Bihar towards achieving its educational aspirations.The development of teacher education holds the key to delivering high-quality education, a foundation upon which the state's progress hinges. Through sustained efforts, cooperation, and visionary steps, Bihar can pave the way for a brighter educational future